Severe Root Resorption after Obturating a Primary Molar Using Zinc Oxide and Eugenol at Different Follow-up Periods – A Case Report - Wahby, Mona Abdel Rehim; Taha, Sherine Ezz Eldin; El Masry, Eman Sayed; Al Gawad, Randa Youssef Abd (Open Access Macedonian Journal of Medical Sciences, 2020)
AIM: The aim of this study is to present severe root resorption following obturation of the primary molar with zinc oxide eugenol (ZOE) at different follow-up periods. CASE REPORT: We present the case of a 6-year-old boy with decayed lower primary molars. Pulpectomy for pulpally involved primary molars was performed. ZOE has been used as root canal filling material and follow-up was done at 3, 6, and 9 months. CONCLUSION: External root resorption was detected at 3 months and the resorptive process continued till 9 months. This finding emphasizes the need for alternative filling material with less irritating properties.